KINERJA RANTAI PASOK DAN PEMASARAN BERBASIS E-COMMERCE DIPETERNAKAN GOATDAY: KINERJA RANTAI PASOK DAN PEMASARAN BERBASIS E-COMMERCE DIPETERNAKAN GOATDAY - Lemboro, Faradila Fatwa Habela; Lestari, Retna Dewi; Afridhianika, Annisa Nugraheni (Journal Science Innovation and Technology (SINTECH), 2025)
Current digital technology advancements are driving the use of e-commerce in the livestock sector, including at Goatday Farm. Goatday Farm currently faces distribution challenges and market restrictions. This study aims to analyze the performance of its e-commerce-based supply chain and marketing, focusing on the principles of visibility and traceability to create an efficient and sustainable system. The research method used is the Supply Chain Network (FSCN) to measure supply chain efficiency and analyze marketing margins to assess distribution effectiveness. The results of this study indicate that with an e-commerce-based marketing and supply chain model/concept, the total supply chain is Rp. 10,500,000 with an output value of Rp. 25,000,000, resulting in a supply chain efficiency of 238%, which means the system is highly efficient. The marketing margin is Rp. 436,500 or 30%, and the farmers' share reaches 70%. By implementing an integrated e-commerce system and proper supply chain principles, Goatday Farm has been able to improve distribution efficiency, information transparency, and product competitiveness in the digital market. Therefore, it is highly recommended that Goatday utilize e-commerce to enhance supply chain efficiency and marketing.